Medication adherence in adolescents in current practice: community pharmacy staff's opinions. (22nd July 2014) - Koster, Ellen S; Philbert, Daphne; Winters, Nina A; Bouvy, Marcel L
Abstract: Objective: To explore pharmacy staff's perspectives regarding medication use behaviour in adolescent patients. Methods: Structured face-to-face interviews were conducted with 170 community pharmacy staff members. Key findings: Medication-related problems in adolescents had been experienced by 80 respondents; non-adherence was frequently mentioned ( n = 73). An important reason for medication-related problems in adolescents not being recognised was that prescriptions are often collected by the parents (with or without the teenager). Solutions suggested by the interviewees to improve adolescents' medication use behaviour included (improving) counselling with emphasis on necessity/benefits of medication ( n = 130) and more direct contact with adolescents instead of parent(s) ( n = 77). Use of digital media for educational purposes or reminder services was suggested to support medication use ( n = 67). Conclusions: Almost half of pharmacy staff experienced problems related to medication use in adolescents. Pharmacy staff see a primary role for counselling on the benefits of therapy but foresee difficulties in obtaining direct contact with adolescents. Use of new media could be useful.